THE ROLE OF CRYPTOCURRENCY IN FINANCIAL OFFENSES - Milimko, Larysa; Breslavets, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the study is to determine the place and role of cryptocurrencies in financial offenses and their counteraction. Research methods: the achievement of the set goal was carried out through the use of specially scientific and general scientific methods of cognition, among which it is necessary to highlight structural-logical, synthesis and analysis, dialectical. Results: cryptocurrency is a virtual, decentralized, convertible, non-fiat currency that operates in a peer-to-peer network, is carried out using digital technologies and is protected by cryptographic encryption methods, with which it is possible to carry out confidential transactions. The advantages of cryptocurrencies during financial transactions are highlighted, as well as threats to the economic security of the state and the international financial system due to the possibility of money laundering obtained by criminal means, financing terrorism, tax evasion and fraud. Ways to improve the activities of bodies to combat financial offenses using cryptocurrencies are proposed. Discussion: based on the established characteristics of cryptocurrency, the advantages and threats of their use are determined, and ways to improve the activities of authorized bodies to combat illegal acts related to the use of cryptocurrencies are identified. The authors conclude that cryptocurrencies are an integral part of the financial system, which has a significant impact on the international economy, and as a result, on the sphere of modern financial offenses. Due to their decentralization, high anonymity and lack of state regulation, digital assets form a favorable field for committing illegal financial transactions. Thus, the role of cryptocurrencies in financial offenses remains tangible, but its impact can be minimized through comprehensive regulation, effective international cooperation and the introduction of control mechanisms that will ensure the transparency of financial transactions in the crypto sector, which, in turn, will contribute to the balance between the innovative development of the cryptocurrency market and the need to prevent the criminal use of digital assets.